Pembuatan Website Untuk Membantu Pemasaran Produk Batik Tulis Dan Ecoprint Pada Umkm Lemayung Di Kelurahan Kepanjenlor Kota Blitar - Nurul Azmy; Arief Bachtiar; Kiky Asmara (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
MSMEs or Micro, Small and Medium Enterprises are businesses owned by persons or legal entities that meet the requirements to be classified as a business. Lemayung is an MSME that sells various kinds of batik products and ecoprints located in KepanjenLor Village, Blitar City. In this community service activity, there is a work program that focuses on utilizing digital marketing. One of the aspects emphasized in this work program is the creation of a website for Lemayung SMEs. It is hoped that this can expand market reach and increase sales of Lemayung MSMEs.